A restoring force model for CFRP seismic-damaged RACFST columns: Theoretical, experimental, and simulation analysis. (June 2022) - Peng, Sheng; Xiong, Zhou; Zeng, Xiang-guo
Abstract: The seismic capacity of frame columns, an important support system of buildings, is a key parameter affecting the collapse of buildings during earthquakes and is used in elastic–plastic seismic response analysis. A restoring force model based on a three-stage skeleton curve for carbon fiber-reinforced polymer (CFRP) and seismic damaged, rectangular recycled aggregate concrete-filled steel tubes (RACFST) frame columns was constructed. Dimensionless processing was used, and the model considered fixed points, the softening point, and the sudden drop in the bearing capacity at the displacement amplitude. The model's accuracy was verified using experiments and OpenSees analysis, and a parametric analysis was conducted. The results show that the values obtained from the experiment, simulation, and calculation are in good agreement, demonstrating the high accuracy of the restoring force model and the OpenSees analysis results. The proposed theoretical restoring force model of the CFRP seismic-damaged RACFST columns accurately reflects the hysteresis load–displacement relationship in the yield phase, peak phase, and damage phase. Thus, it can be used to analyze the seismic capacity and plastic seismic response of the reinforced RACFST structures with seismic damage.